2022
DOI: 10.3390/ijms23168902
|View full text |Cite
|
Sign up to set email alerts
|

New Possibilities in the Therapeutic Approach to Alzheimer’s Disease

Abstract: Despite the fact that Alzheimer’s disease (AD) is the most common cause of dementia, after many years of research regarding this disease, there is no casual treatment. Regardless of the serious public health threat it poses, only five medical treatments for Alzheimer’s disease have been authorized, and they only control symptoms rather than changing the course of the disease. Numerous clinical trials of single-agent therapy did not slow the development of disease or improve symptoms when compared to placebo. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 181 publications
0
21
0
Order By: Relevance
“…Our paper confirms the clinical value of 18 F-FDG brain PET/CT as an essential diagnostic first step to contribute to the differential diagnosis of dementia disorders also in the amyloid PET and biological markers (i.e., amyloid and tau protein) era since, as it is well known, accurate and early diagnosis of Alzheimer disease in respect of Mild Cognitive Impairment is crucial for improving the condition of patients. The combined use of semi-quantitative analysis of 18 F-FDG PET and automatic classification seems to be a supportive tool for clinical diagnosis in order to consider effective preventive early measures to delay the appearance of the full-blown disease or to suggest further investigations such as amyloid PET or more advanced treatments and therapeutic approaches [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our paper confirms the clinical value of 18 F-FDG brain PET/CT as an essential diagnostic first step to contribute to the differential diagnosis of dementia disorders also in the amyloid PET and biological markers (i.e., amyloid and tau protein) era since, as it is well known, accurate and early diagnosis of Alzheimer disease in respect of Mild Cognitive Impairment is crucial for improving the condition of patients. The combined use of semi-quantitative analysis of 18 F-FDG PET and automatic classification seems to be a supportive tool for clinical diagnosis in order to consider effective preventive early measures to delay the appearance of the full-blown disease or to suggest further investigations such as amyloid PET or more advanced treatments and therapeutic approaches [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin inhibition A β The aggregation mechanism may be in A β The specific mechanism of a link after generation needs to be further studied. In general, animal studies have shown promising findings on the physiological and behavioral enhancement of cognition [7]. The effectiveness in human body needs to be further explored.…”
Section: Curcuminmentioning
confidence: 99%
“…Blood-based biomarkers have an advantage in this regard, but to date, they do not achieve the same accuracy; there is still no certainty whether or when an asymptomatic person with an elevated biomarker level might develop AD symptoms. However, a combination of blood-based biomarkers has a good chance of achieving the same accuracy as PET or CSF biomarkers in the near future (Doroszkiewicz & Mroczko, 2022).…”
Section: Diagnostics-related Ethical Issuesmentioning
confidence: 99%